Determinasi Return On Asset (ROA), Return On Equity (ROE), dan Net Profit Margin (NPM) Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Sektor Consumer Cyclicals Yang Terdaftar di BEI Periode 2021-2023 - Dharma, Ni Putu Gita Anggraestarni; Riswan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of financial performance as measured by Return On Asset (ROA), Return On Equity (ROE), and Net Profit Margin (NPM) on the timeliness of financial reporting in 14 Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The sampling method used was purposive sampling, and data analysis was carried out using logistic regression. The results of the study indicate that ROA, ROE, and NPM significantly affect the failure to fulfill the time of financial reporting. The timeliness of financial reporting is important to maintain the trust of investors and other stakeholders. This study contributes to the literature on the effect of financial performance on corporate reporting in reporting, as well as providing insight for corporate management to improve transparency and accountability through timely reporting.